2008
DOI: 10.1063/1.3006007
|View full text |Cite
|
Sign up to set email alerts
|

Electric-field-induced resonant tunneling lifetime in semiconductor multibarrier systems

Abstract: A study on the variation in resonant tunneling lifetime (RTL) with the applied electric field is presented for the GaAs/AlxGa1−xAs periodic multibarrier systems (MBSs). The variation shows a contrasting behavior of lifetime for quasiresonant states situated at the miniband edge and those for well inside the miniband. For fields larger than 500 kV/m, the RTL corresponding to the midband state increases with the increase in electric field, whereas it decreases with the increase in field for the states near the m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
11
0

Year Published

2009
2009
2023
2023

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 11 publications
(14 citation statements)
references
References 29 publications
3
11
0
Order By: Relevance
“…Considering the energy‐time uncertainty principle Δ E Δ t ∼ ħ /2, we can argue that charge carriers tunneling through the 2D barrier momentarily stay in the tunnel junction for Δ t ∼ ħ /(2Δ E ), which is related to the resonant tunnel lifetime in a semiconductor tunnel junction where Δ E is the half‐width half‐maximum of the transmission coefficient. [ 42 ] During this transitory stay, charges travel by λ = v Δ t , later expressed as λ = ħ /(2 m *Δ E ) 1/2 by combining the de Broglie wave p = m * v = ħ /λ and the uncertainty principle for Δ t ; namely, a lighter effective mass indicates that tunneling charges can transport deeper into the barriers. For the particular case that the thickness of an insulating layer d becomes thinner than λ, the penetration depth λ can naturally be replaced by d .…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Considering the energy‐time uncertainty principle Δ E Δ t ∼ ħ /2, we can argue that charge carriers tunneling through the 2D barrier momentarily stay in the tunnel junction for Δ t ∼ ħ /(2Δ E ), which is related to the resonant tunnel lifetime in a semiconductor tunnel junction where Δ E is the half‐width half‐maximum of the transmission coefficient. [ 42 ] During this transitory stay, charges travel by λ = v Δ t , later expressed as λ = ħ /(2 m *Δ E ) 1/2 by combining the de Broglie wave p = m * v = ħ /λ and the uncertainty principle for Δ t ; namely, a lighter effective mass indicates that tunneling charges can transport deeper into the barriers. For the particular case that the thickness of an insulating layer d becomes thinner than λ, the penetration depth λ can naturally be replaced by d .…”
Section: Resultsmentioning
confidence: 99%
“…Considering the energy-time uncertainty principle ΔEΔt ∼ ħ/2, we can argue that charge carriers tunneling through the 2D barrier momentarily stay in the tunnel junction for Δt ∼ ħ/(2ΔE), which is related to the resonant tunnel lifetime in a semiconductor tunnel junction where ΔE is the half-width half-maximum of the transmission coefficient. [42] During this transitory stay, charges travel by λ = vΔt, later expressed as λ = ħ/(2m*ΔE) 1/2 by combining the de Broglie wave p = m*v = ħ/λ and the uncertainty principle for Δt; namely, a lighter effective mass indicates that tunneling charges can transport deeper into the barriers. For the particular case that the thickness of an insulating layer d becomes thinner than λ, the penetration depth λ can naturally be replaced by d. Following this simple heuristic argument, we www.advelectronicmat.de can make two postulates: i) the bulk effective mass m* defines the critical thickness d c = ħ/(2m*ΔE) 1/2 at which the vertical quantum tunneling exhibits a crossover from bulk to 2D multiband transport, and ii) the "equivalent" charge carrier effective mass in an atomically thin SCTMD insulator reconfigures as m* 2D = ħ 2 /(2ΔEd 2 ).…”
Section: Redefinition Of Vertical Effective Mass In Ultrathin Sctmdsmentioning
confidence: 99%
“…Due to the chiral nature of these pseudo‐particles, graphene crystallites exhibit a number of exceptional electronic properties 3–11 and deserve special attention for theoretical and experimental studies. Among the various electronic properties, transport phenomena based on resonant tunnelling are now well established and the understanding of different time‐dependent aspects of tunnelling is now almost clear for conventional semiconductor systems 12. However, only little effort has been expended on the study of the resonant behaviour of these chiral particles in graphene systems.…”
Section: Introductionmentioning
confidence: 99%
“…During last two decades or so, the resonant tunneling has become an important facet of condensed matter physics [1,2,3,4,5,6,7,8,9]. In the recent years the investigation of the lifetime of states corresponding to resonant tunneling has drawn considerable attentions [1,2,3,5,6,7,8].…”
Section: Introductionmentioning
confidence: 99%
“…In the recent years the investigation of the lifetime of states corresponding to resonant tunneling has drawn considerable attentions [1,2,3,5,6,7,8]. While studying the resonant tunneling relativistically, it has been found that the resonant states occur in lower energies as compared to the non-relativistic (NR) ones [10,11].…”
Section: Introductionmentioning
confidence: 99%